Family reunion in a university law clinic: a model for law schools? - Marson, James; Ferris, Katy; Tudor, Clare (EJoCLI, 2017)
This paper outlines the establishing of a law clinic to assist individuals with their application under the refugee family reunion (RFR) provision. We consider that a significant gap exists in the scope of university law clinics to provide a dedicated RFR service, a gap which extends to service providers generally in many regions in the UK. The removal of legal aid for family reunion applications has negatively affected the efficacy of refugees and those with humanitarian protection status to be reunited with their families (a right provided under international law to which the UK is a signatory). Family reunion is a very current issue of concern given global developments and the political instability in many countries, and it is also a topic which is at the very heart of social justice, a philosophy which underpins many law clinics in universities. Law clinics allow universities and their students to use their talents and resources to positively change the lives of people in their local communities. Significantly, broadening the scope of law clinics to offer a RFR service will enrich the learning experience of staff and students involved in RFR clinics, help to produce the next generation of lawyers, policy and decision-makers with an awareness of the issues facing refugees and the human perspective of the crises affecting them, and facilitate research opportunities through effective data collection and analysis. Subsequent outputs can positively affect national policy on immigration, asylum, legal aid, and engagement with, and the education of, the public.